Root hairs enable high transpiration rates in drying soils. Issue 3 (31st July 2017) - Carminati, Andrea; Passioura, John B.; Zarebanadkouki, Mohsen; Ahmed, Mutez A.; Ryan, Peter R.; Watt, Michelle; Delhaize, Emmanuel
Summary: Do root hairs help roots take up water from the soil? Despite the well‐documented role of root hairs in phosphate uptake, their role in water extraction is controversial. We grew barley ( Hordeum vulgare cv Pallas) and its root‐hairless mutant brb in a root pressure chamber, whereby the transpiration rate could be varied whilst monitoring the suction in the xylem. The method provides accurate measurements of the dynamic relationship between the transpiration rate and xylem suction. The relationship between the transpiration rate and xylem suction was linear in wet soils and did not differ between genotypes. When the soil dried, the xylem suction increased rapidly and non‐linearly at high transpiration rates. This response was much greater with the brb mutant, implying a reduced capacity to take up water. We conclude that root hairs facilitate the uptake of water by substantially reducing the drop in matric potential at the interface between root and soil in rapidly transpiring plants. The experiments also reinforce earlier observations that there is a marked hysteresis in the suction in the xylem when the transpiration rate is rising compared with when it is falling, and possible reasons for this behavior are discussed.